Antecedents and Consequences of Mimicry: A Naturalistic Interaction Approach. Issue 2 (March 2015) - Kurzius, Elena; Borkenau, Peter
Abstract: Mimicking, that is showing the same nonverbal behaviour as one's interaction partner, is related to trait Affiliation, but there are no previous investigations on its relations to broader concepts of personality. In this study, personality was assessed in terms of the Big Five and the two interpersonal dimensions Affiliation and Dominance. Dyads of unacquainted participants completed a task, several of their behaviours being coded every 10 s. Moreover, the interactants were instructed either to cooperate or to compete, and their performance and liking were measured. Using multilevel modelling, mimicry coefficients were estimated (Level 1) and predicted from personality (Level 2) and the situational context (Level 3). In addition, performance and being liked were predicted from mimicry and the context. Mimicry turned out to be widespread, being predicted by personality traits for some behaviours. In turn, mimicry predicted performance and being liked, some of these effects also depending on the context. Copyright © 2015 European Association of Personality Psychology